Preparation and Thermal Properties of Polyethylene Terephthalate/Huntite-Hydromagnesite Composites - KAHRAMAN, MEMET VEZİR; MADAKBAŞ, SEYFULLAH (WILEY, 2016)
In this report, it was aimed to the improve thermal stability of polyethylene terephthalate (PET) by adding huntite/hydromagnesite minerale. PET/huntite/hydromagnesite composites were prepared by adding various proportions of huntite/hydromagnesite to PET. The chemical structures of the composites were characterized by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis. Thermal properties of the composites were determined by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Glass-transition temperatures and char yields increased with the increase of the huntite/hydromagnesite content in the composites. The surface morphologies of the composites were investigated by a scanning electron microscopy. The obtained results proved that the composite system is more thermally stable than the pure PET itself. (C) 2015 Society of Plastics Engineers
Keywords: NANOCOMPOSITES; POLY(ETHYLENE-TEREPHTHALATE); MORPHOLOGY; HUNTITE; PET